Integrative and complementary health practices in the city of Belém-PA/Brazil: situational profile of phytotherapy in the municipal health unit of Jurunas (Research, Society and Development, 2022)
Objective: Demonstrate the implementation of Integrative and Complementary Health Practices - ICHP in the Municipality of Belém and the situational profile of the offer of phytotherapy in the Municipal Health Unit of the Jurunas neighborhood. Methodology: An observational and descriptive study of the data obtained from questionnaires and patient care records was carried out from June to September 2022. Result: The official implementation of ICHP in the city of Belém starts only in 2021, offering a phytotherapy service structured in the pharmaceutical office at UMS do Jurunas. Most health professionals interviewed were aware of phytotherapy, but there was a need for updating. Regarding users, 40% reported having used the phytotherapy service. Most medical records indicated anxiety and depression as admission diagnosis, being prescribed the herbal medicine calmam and the traditional herbal product, passion fruit, and associated with some medicinal plants for this purpose. The profile of users consisted mostly of women and the age group of 30 to 59 years. Conclusion: The offer of ICHP, especially phytotherapy, is still a challenging practice for municipal management, but it has a promising future in expansion, as long as there is investment in the qualification of prescribing professionals and the offer of a list of medicines and medicinal plants.